Abnormal blood viscosity and haemostasis in long-standing retinal vein occlusion. Issue 3 (March 1983) - Trope, G E; Lowe, G D; McArdle, B M; Douglas, J T; Forbes, C D; Prentice, C M; Foulds, W S
Abstract : Blood viscosity and several haemostatic factors were measured in 42 patients with long-standing retinal vein occlusion and 33 control subjects. Blood viscosity, haematocrit, plasma viscosity, fibrinogen, fibrinopeptide A, and beta-thromboglobulin were increased in the 20 subjects with capillary nonperfusion or new vessels, but not in the 22 subjects without these complications. Patients with nonperfusion or new vessels also had a lower platelet count than patients without complications. Increased levels of factor VIII antigen and decreased levels of antithrombin III were found in the retinal vein occlusion group as a whole. These findings suggest that blood viscosity, platelets, and coagulation may be involved in retinal vein occlusion and its vascular complications.